Assessment of the current state of rangelands in Karakalpak Ustyurt, Uzbekistan - NODIRA K. RAKHIMOVA; TASHKHANIM RAKHIMOVA; KHABIBULLO F. SHOMURODOV; BEKHZOD А. ADILOV; VASILA K. SHARIPOVA; UMIDA SH. SAITJANOVA; BEKHRUZ SH. KHABIBULLAEV; JASUR S. SADINOV; FARRUKH I. POLVONOV; AZAMAT T. SULTAMURATOV (Biodiversitas Journal of Biological Diversity, 2023)
Abstract. Rakhimova NK, Rakhimova T, Shomurodov KhF, Adilov BA, Sharipova VK, Saitjanova USh, Khabibullaev BSh, Sadinov JS, Polvonov FI, Sultamuratov AT. 2023. Assessment of the current state of rangelands in Karakalpak Ustyurt, Uzbekistan. Biodiversitas 24: 3835-3843. Assessing the current state of rangelands common in the territory of Karakalpak Ustyurt, Uzbekistan is of great importance in connection with intense land degradation and climate change. The article is devoted to study the main attributes and indicators for qualitative and quantitative assessment of rangelands including the current state of vegetation, soil cover and use of fodder resources. The studied types of rangelands are common on gray-brown desert soils, takyrs, and salt marshes, characterized by high gypsum content. Rangeland vegetation of Ustyurt, composed mainly of Artemisia terrae-albae Krasch., Anabasis salsa (Ledeb.) Benth. ex Volkens, Xylosalsola arbuscula (Pall.) Tzvelev, Salsola arbusculiformis Drobow, Caroxylon orientale (S.G. Gmel.) Tzvelev, ephemera, and other plant species, is the main fodder source for Karakul sheep and camels. The nutritional value of rangeland varieties is quite high in spring, it is characterized by an increased content of digestible protein in this period and decreases towards autumn, while the above-ground yield of species reaches its maximum growth. Autumn and winter-spring precipitation play the main role in the fodder productivity of rangelands. The productivity of rangelands depends on the favorable climatic conditions of the year, if more precipitation falls, the year will be more favorable for the growth and development of plants.